Teknik Grounding untuk Mengurangi Kecemasan pada Remaja - Umy Yonaevy; Ratih Prananingrum (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
Anxiety is a common mental disorder in adolescents that can have a negative impact. This study evaluated the effectiveness of grounding technique psychoeducation in reducing anxiety in 30 adolescents aged 14-17 years. Using a quasi-experimental design with pre-test and post-test measurements, participants were divided into an experimental group that received grounding technique psychoeducation and a control group. Results showed the experimental group experienced a significant reduction in anxiety scores after the intervention, with a large effect size. These findings are consistent with previous research and suggest that grounding technique psychoeducation can be an effective intervention to reduce anxiety in adolescents. However, further research is still needed to evaluate the long-term effects, compare with other interventions, and investigate the underlying mechanisms.